2018
DOI: 10.1089/end.2017.0602
|View full text |Cite
|
Sign up to set email alerts
|

Mini Versus Standard Percutaneous Nephrolithotomy: The Impact of Sheath Size on Intrarenal Pelvic Pressure and Infectious Complications in a Porcine Model

Abstract: Mini-PCNL was associated with higher intrarenal pressures and higher risk of end organ bacterial seeding in the setting of an infected collecting system. This suggests a higher potential for infectious complications in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
0
22
0
6
Order By: Relevance
“…High intrarenal pressures have also been associated with infectious complications. In a study comparing mini-PCNL to regular PCNL, mini-PCNL procedures demonstrated higher intra-renal pressures and had higher rates of end-organ seeding with bacteria which originated in the kidney (15). Furthermore, sustained time at high intra-renal pressures have been associated with post-operative fever (8).…”
Section: Discussionmentioning
confidence: 99%
“…High intrarenal pressures have also been associated with infectious complications. In a study comparing mini-PCNL to regular PCNL, mini-PCNL procedures demonstrated higher intra-renal pressures and had higher rates of end-organ seeding with bacteria which originated in the kidney (15). Furthermore, sustained time at high intra-renal pressures have been associated with post-operative fever (8).…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al focused specifically on the differences between standard and mini PCNL and found comparatively higher intrarenal pressures for mini PCNL, and also noted that mini PCNL procedures were more likely to be associated with postoperative sepsis [36]. In a porcine model, mini PCNL was associated with higher intrarenal pressures and higher risk of organ bacterial seeding in the setting of an infected collecting system, suggesting a higher potential for infectious complications [37]. Suction through the sheath or other intrarenal pressureregulating systems (e.g., new designs of the sheath) may overcome the concerns regarding pressure in mini PCNL, and suction through the sheath during miniaturized PCNL definitely deserves attention with respect to both efficacy and safety [38][39][40].…”
Section: Safety Aspects Of Lithotripsy During Miniaturized Pcnlmentioning
confidence: 99%
“…The development of surgical techniques and instruments continues to play a major role in the popularization of PCNL and RIRS [48,50]. mPCNL is de ned as PCNL performed using Amplantz sheaths with a diameter of 14-20 Fr [3,51]. mPCNL has the advantage of reducing complications that may arise from larger instruments and sheaths [4].…”
Section: Discussionmentioning
confidence: 99%